1998
DOI: 10.1007/s005200050167
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for psychological distress in ambulatory lung cancer patients

Abstract: Although there is a need for systematic research on the psychosocial issues faced by lung cancer patients, there have been few studies in this area. The objective of the present study was to investigate potential predictors of psychological distress among ambulatory lung cancer patients. The variables examined included the patients' characteristics, coping responses, and social support factors. Lung cancer patients completed the Profile of Mood States (POMS) and the Mental Adjustment to Cancer scale (MAC scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 23 publications
3
41
0
4
Order By: Relevance
“…It is possible, for instance, that lower levels of symptoms and distress resulted in higher perceived self-efficacy, or that other unmeasured factors led to both higher self-efficacy and lower levels of symptoms and distress. However, clinical observations suggest that feelings of helplessness and loss of control are a frequent problem for patients coping with cancer (Akechi et al, 1998;Uchitomi et al, 2003). The findings of this study suggest that clinicians interested in understanding how lung cancer patients adapt to their illness may benefit by attending to patients' perceptions of self-efficacy.…”
Section: Discussionmentioning
confidence: 81%
“…It is possible, for instance, that lower levels of symptoms and distress resulted in higher perceived self-efficacy, or that other unmeasured factors led to both higher self-efficacy and lower levels of symptoms and distress. However, clinical observations suggest that feelings of helplessness and loss of control are a frequent problem for patients coping with cancer (Akechi et al, 1998;Uchitomi et al, 2003). The findings of this study suggest that clinicians interested in understanding how lung cancer patients adapt to their illness may benefit by attending to patients' perceptions of self-efficacy.…”
Section: Discussionmentioning
confidence: 81%
“…Younger patients and women report higher levels of distress [7,11,14,15], and individuals with lung cancer, compared to individuals with other cancer diagnoses, also report higher levels of distress [15,17]. Approximately 43% of patients with lung cancer report clinically-significant levels of distress [15,18], compared to about 33% of patients with breast cancer and 32% of patients with colon cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…Distress has been defined as "a multifactorial, unpleasant experience of an emotional, psychological, social, or spiritual nature that interferes with the ability to cope with cancer, its physical symptoms, and its treatment" [1,2]. In the oncology context, distress is multifactorial, as numerous areas in a patient's life contribute to his or her experience of distress, including physical symptoms, disease severity, treatment [3,4]; physical activity level / performance status [5][6][7]; social support (for a review see [8]); and psychological factors such as optimism [9,10], coping style [11,12], and pre-morbid or current depression [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support from a coresident may influence both the quality of life of cancer sufferers and their need for external services, including in-patient admission. Studies of particular patient groups from a range of settings have reported that cancer patients who live alone report more distress, poorer adjustment to diagnosis and have a poorer quality of life than those living with others (Forsberg and Cedermark, 1996;Akechi et al, 1998;Rustoen et al, 1999;Sollner et al, 1999;Sarna et al, 2002). Living arrangements may also influence chance of a home death, for which many people with cancer report a preference (Davison et al, 2001; Serra-Prat, Gallo and Picaza, 2001).…”
mentioning
confidence: 99%